1988
DOI: 10.3109/02770908809071365
|View full text |Cite
|
Sign up to set email alerts
|

Original Articles: High-Dose Methylprednisolone as Initial Therapy in Patients with Acute Bronchospasm

Abstract: The use of steroids in treating acute respiratory obstruction is still controversial. In this double-blind controlled trial, we decided to examine the beneficial effects of a single large dose of methylprednisolone (MSSP), using objective criteria. In the emergency setting, methylprednisolone (30 mg/kg) has been shown to decrease the need for hospital admission in patients with acute bronchospasm. No difference in this improvement was seen among patients in the steroid-dependent or non-steroid-dependent popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…These results are interesting because the concentrations used were within the therapeutic range if methylprednisolone is given in bolus megadoses (see e.g. Barile and Lavalle, 1992;Bracken et al, 1992;Schneider et al, 1988). The underlying mechanism remains unexplained, although we have proposed that methylprednisolone works by direct effects on membranes.…”
Section: Top-down Control Analysismentioning
confidence: 61%
“…These results are interesting because the concentrations used were within the therapeutic range if methylprednisolone is given in bolus megadoses (see e.g. Barile and Lavalle, 1992;Bracken et al, 1992;Schneider et al, 1988). The underlying mechanism remains unexplained, although we have proposed that methylprednisolone works by direct effects on membranes.…”
Section: Top-down Control Analysismentioning
confidence: 61%
“…Hence, data in terms of lung function are more encouraging. [4041] In terms of effect on exacerbation relapse after discharge from the ED, most studies showed less relapse with systemic corticosteroids[3542] although others did not. [43] One important issue with all these studies is the low number of recruited patients.…”
Section: Clinical Evidence Of the Effect Of Corticosteroids In Acute mentioning
confidence: 99%
“…2,3 Furthermore, although corticosteroids are traditionally thought to exert their effect over hours rather than minutes, there is theoretical and clinical evidence of acute treatment effects. 46 A meta-analysis 7 summarizing 12 randomized trials has shown that the use of SC within 1 hour of ED arrival significantly improves pulmonary function and reduces the odds of hospital admission by 60%. The evidence also suggests little benefit for higher doses 8 or for intravenous treatment.…”
Section: Introductionmentioning
confidence: 99%